Whakarongo : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters of Māori Visual Arts at Massey University, Manawatu, New Zealand - Potaka, Maihi (Massey University, 2021)
The symbolic characteristics and elegant design of kōwhaiwhai pique my curiosity, through the expression of kōwhaiwhai I have recognised the beauty in the nature of its composition. I believe the values seen in the compositions of kōwhaiwhai are aesthetic and give pleasure when viewing the patterns therefore, uplifting the well-being of the viewer. I propose that my kōwhaiwhai designs have healing properties through the visual senses, in the same way that rongoā māori covers senses including, sound – taonga pūoro that is used in a healing context, taste – digestion of herbal remedies, touch – the application of ointment on skin, and scent – the use of oils for our sense of smell. This exhibition report sheds light on the functions of kōwhaiwhai within a rongoā māori context. Over the course of this Masters research, I have envisioned and created a series of works that invoke a positive state of mind based on the feel of the colours and patterns with hopes of them being utilised as a form of rongoā māori. These patterns are intended to assist in the connection between the many aspects of our well-being with the hope that the shapes and patterns can help re-balance and strengthen our people to blossom to their full potential. “Whatu” is a methodology I created for producing kōwhaiwhai designs that create pleasure and enjoyment when viewed. Te mauri o te manawa, whakaaro pai, hangarite, taurite, korikori, and hononga are the values included in this methodology. These values, as well as my creation process, act as a basis and are reflected in my show “Whakarongo”. My creation process mimic five different states of mauri, these are as follows: ● Mauri noho – inactiveness, broad ideas ● Mauri oho – awakening of an idea ● Mauri rere – drafts of the physical manifestation of the idea ● Mauri tau – completion of composition based on the idea ● Mauri ora – fabrication and execution of the idea. The techniques and dynamics used within my exhibition to achieve aesthetic kōwhaiwhai designs are abstraction, symmetry, contrast, and visual metaphors. As a result, these techniques demonstrate how kōwhaiwhai can connect with rongoā māori. I believe there are definite connections in this exegesis that relate to the elevation of well-being when viewing my kōwhaiwhai works, thus recognising kōwhaiwhai as a form of rongoā māori.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)